Formation pathways, ecosystem functions, and the impacts of land use and environmental stressors on soil aggregates - Ponyane, Patience; Dina Ebouel, Ferdinand J.; Eze, Peter N. (Frontiers in Environmental Science, 2025)
Soil aggregates have been identified as a critical biogeochemical indicator of soil health, playing a pivotal role in addressing numerous environmental challenges and maintaining ecological equilibrium within soil environments. However, there is a paucity of scientific literature that have provided a comprehensive understanding of the role of soil aggregates in the environmental and ecosystem functions of soils. The objective of this review article therefore is to provide a comprehensive overview of the environmental and ecosystem functions of soil aggregates. Subsequently, the effects of land use and/or changes in land use in the delivery of these functions were examined. It is established that soil aggregates play a pivotal role in five environmental and ecosystem functions within the soil, including: (i) the provision of habitat for soil microorganisms by regulating niche formation and predation; (ii) the long-term sequestration of soil organic carbon (SOC) within microaggregates, preserved in macroaggregates; (iii) the regulation of nutrient exchange at the soil‒plant‒water‒atmosphere interface; (iv) the immobilisation of pollutants such heavy metal; and (v) the regulation of water movement in the soil. Land use has a major influence on the ability of soil aggregates to deliver these functions. The restoration of natural ecosystems (forests, grasslands, wetlands) has an overall positive effect, while farming, on the other hand, has a negative effect. Nevertheless, adopting sustainable management practices such as agroforestry, the use of organic soil amendments and reduced or no tillage can significantly reduce the adverse effects observed. Future research should look into how soil aggregates help capture carbon dioxide in dry areas through the inorganic carbon pathway and work on creating large-scale models to observe how these aggregates change and their effects on the environment and ecology.